Edukasi Prosedur Persiapan Anestesi Spinal Menggunakan Buku Saku Untuk Meningkatkan Pengetahuan pada Pasien Sectio Caesarea di RSU Siaga Medika Purbalingga - Sutrisno Sutrisno; Tophan Heri Wibowo; Rahmaya Nova Handayani (Journal of Health, Medical, and Psychological Studies, 2026)
Caesarean section is a surgical procedure that commonly uses spinal anesthesia as the method of analgesia. Limited patient knowledge regarding spinal anesthesia preparation can increase anxiety and reduce both physical and psychological readiness prior to surgery. This community service activity aimed to improve the knowledge of preoperative caesarean section patients through education using a pocketbook at RSU Siaga Medika Purbalingga. The method applied was direct education with a pre-test and post-test design involving 25 preoperative patients. The results showed a significant improvement in participants’ knowledge levels. The average score increased from 65.60 before education to 87.20 after education, with a difference of 21.60. Before the intervention, knowledge levels were categorized as good (16%), moderate (56%), and poor (28%). After the intervention, the proportion of good knowledge increased to 88% and moderate to 12%, with no participants remaining in the poor category. These findings indicate that pocketbook-based education is effective in enhancing patient knowledge. This simple, practical, and accessible medium supports better understanding and improves patient readiness before surgery, contributing to higher-quality preoperative care based on a patient-centered approach.